2006
DOI: 10.2215/cjn.01220406
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis and Peritoneal Dialysis

Abstract: This study was undertaken to examine patient satisfaction with peritoneal dialysis (PD) and hemodialysis (HD) therapies, focusing attention on the positive and negative impact of the therapies on patients' lives. Patients were recruited from a free-standing PD unit and two free-standing HD units. A total of 94% (n ‫؍‬ 62) of eligible PD and 84% (n ‫؍‬ 84) of eligible HD patients participated. HD patients were significantly older and had higher Charlson Comorbidity Index scores than the PD patients, but there w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
131
1
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(145 citation statements)
references
References 21 publications
8
131
1
5
Order By: Relevance
“…There is evidence in literature that supports an argument that peritoneal dialysis is associated with better QoL than the hemodialysis [32][33][34][35][36][37][38]; however, there is a report which indicates that there is no such association [39].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence in literature that supports an argument that peritoneal dialysis is associated with better QoL than the hemodialysis [32][33][34][35][36][37][38]; however, there is a report which indicates that there is no such association [39].…”
Section: Discussionmentioning
confidence: 99%
“…26 Whether PD confers better psychological outcomes than HD is still largely contentious. In some studies, it has been reported that patients with HD experience higher symptoms of depression and anxiety than that of patients on PD, 27,28 in line with dialysis modality differences in QoL. 29 Patients with HD have also been shown to have higher hospitalization rates for depression and affective disorders.…”
Section: -25mentioning
confidence: 98%
“…Legitimate concerns need not preclude education for these patients about novel and creative choices such as in-center nocturnal dialysis, which offers the ability to independently dialyze within a protective environment that provides adequate supervision. It should be noted that several studies have found increased satisfaction with home therapies as compared with ICHD (15)(16)(17). For instance, Rubin and colleagues found that PD patients were much more likely than ICHD patients to rate their dialysis care as excellent (16).…”
Section: Choice Of Therapymentioning
confidence: 99%